PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN MANGROVE DI DUSUN SETINGGA ASIN DESA SEBUBUS KECAMATAN PALOH KABUPATEN SAMBAS - Suraimah, .; Thamrin, Eddy; M, Iskandar A (JURNAL HUTAN LESTARI, 2019)
Mangrove forests are tropical coastal vegetation communities, which are dominated by several types of mangrove trees that are able to grow and develop in muddy coastal tidal areas. In order to preserve the biological and ecological functions of the mangrove forest ecosystem, a rational approach is needed in which a rational approach in its utilization involves communities around the area. Hamlet of Setingga Asin Sebubus Village, Paloh Subdistrict, Sambas Regency is one of the hamlets that has a mangrove forest area. The majority of the hamlet Setingga Asin people live as farmers, entrepreneurs and fishermen. People around the forest use it as additional livelihoods such as searching for shrimp, crabs, shellfish, kepah and nipah as the main ingredients for making roofs. The existence of the relationship between the community and the existence of mangrove forests raises the perception of the community in an effort to maintain and preserve the existence of the mangrove forest itself. Therefore, this study aims to determine the public perception of the existence of mangrove forests in Hamlet of Setingga Asin, Sebubus Village, Paloh Subdistrict, Sambas Regency and to know the factors that influence people's perceptions. The study used a survey method with interview techniques for 73 family heads in Hamlet Setingga Asin. Sampling of respondents is done by purposive sampling technique. The data analysis used was descriptive analysis and inferential analysis of the Kendall Tau correlation. The results showed that community perceptions of the existence of mangrove forest in hamlet Setingga Asin, Sebubus Village, Paloh Subdistrict, Sambas Regency tend to be neutral, this is because the community basically realizes that they depend on the surrounding mangrove forest's biological resources. However, the community does not understand that these resources need to be managed sustainably so that the benefits can be obtained sustainably.Keywords: community perception, conservation, mangrove, utilization.